The Mediation of Novelty-Seeking Tendencies in Tourists’ Revisit Intention: A Case from Singapore - Abubakar, Ayodele M. (2014)
Prior research evidence has been set on the relationship between perceived values, satisfaction, and destination image and revisit intentions of tourists. Yet, limited research focused on the mediation role of novelty-seeking tendencies between perceived values, satisfaction, and destination image to revisit intentions. To respond this call to explore the mediation role of novelty-seeking tendencies, this study is designed to extend the previous research by examining the relationship between perceived values, satisfaction and destination image to revisit intentions. This research probes into the mediation of novelty-seeking tendency theory when examining the revisit intentions of tourist in Singapore. 324 respondents were sought using questionnaires as a tool using convenient sampling. The research hypotheses were tested using PLS estimation technique version 2.0 while descriptive analysis was done using SPSS statistical software version 20. This research revealed the significant effect perceived value, satisfaction, and destination image has on novelty-seeking tendencies. Though, satisfaction is found to have a direct relationship with revisit intention. Therefore, novelty-seeking tendencies mediates the relationship between perceived value and destination image to revisit intention although there is no mediation found of novelty-seeking tendencies between satisfaction and revisit intention. The discussion collates the empirical collates the empirical evidence and contribution. Theoretical and practical implications followed by recommendations for future research are provided.